Synthesis and Mechanical Properties of Cast Alumina Nano-particle Reinforced Metal Matrix Composites. (2015) - Ghanaraja, S.; Ray, Subrata; Nath, S.K.
Abstract: The development of Lightweight metal matrix nano-composites (MMNCs) based on aluminium and magnesium has emerged as an important class of materials, finding increasing applications in automobile, aero-space and space industries, in their quest for achieving better fuel economy. The present study investigates the outcome of mechanical properties in a composite, reinforced nano particle. High energy milling using vibratory disc mill RS200, (Retsch, Germany) for 600 minutes at 700 rpm of manganese dioxide particles with excess of aluminium powder weight ratio of 1:7 ensures that nanoparticles generated, either of MnO2 or alumina, are mostly separate and surrounded by aluminium particles. The milled powder when added to aluminium alloy melt, the excess aluminium particles will melt leaving behind separate oxide nanoparticles without significant agglomeration. Micrographs observed under Transmission Electron Microscope (TEM) have revealed the presence of nano-sized γ-alumina particles as a consequence of milling. The amount of addition varies from 1 to 3 wt % in steps of 1 wt % of particles after drying is added to molten metal/alloy and the resulting slurry is cast in a mold to get cast nano-composite. The microstructure of cast composites when analyzed by TEM and FE-SEM, confirm separate occurrence of nano-particles without agglomeration and its mechanical properties show significant improvement in terms of yield strength, tensile strength and ductility.